Malnutrition Matters in Canadian Hospitalized Patients: Malnutrition Risk in Hospitalized Patients in a Tertiary Care Center Using the Malnutrition Universal Screening Tool. (7th August 2015) - Rahman, Adam; Wu, Thomas; Bricknell, Ryan; Muqtadir, Zack; Armstrong, David
Abstract : Background: Malnutrition is common in Canadian hospitalized patients, yet system‐wide malnutrition screening is not mandatory in Canada. Aims : Our goal was to define the point prevalence of malnutrition risk at a major tertiary care center in Hamilton, Ontario, using the Malnutrition Universal Screening Tool (MUST) to determine feasibility of hospital‐wide screening in the Canadian context. Methods : After research ethics approval was obtained, we arranged for a clinical nutrition support team to conduct the MUST screening on all inpatients at Hamilton Health Sciences, Juravinski site, a large academic acute care hospital. Results : A total of 315 patients were included (female, n = 160 [51%]; male, n = 155 [49%]; average age, 71 years). We identified 31% at high risk for malnutrition and 14% at medium risk, keeping with reported rates of malnutrition in the literature. Survey of dietitians and interns indicated that the MUST was easy to use and perform and that they had support of their unit supervisors. All respondents thought that the screen was useful and they wanted to repeat it. Conclusion : The MUST is an easy and efficient way to define point prevalence of malnutrition risk in Canadian hospitalized patients. Moving to system‐wide nutritional screening will bring about the best practices in nutrition care with the involvement of key stakeholders and decision makers. Nutritional screening will allow us to utilize nutrition resources more efficiently, engage administrators in addressing shortfalls in nutrition care, and form a baseline for which to measure the efficacy of future nutritional interventions.